An investigation and evaluation of three integrated library systems for the Human Sciences Research Council Information Services - Sani, Cecilia Maria (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MPhil (Information Science))--University of Stellenbosch, 2006.